Revolutionaries, Monarchists, and Chinatowns Chinese Politics in the Americas and the 1911 Revolution - Ma, L. Eve Armentrout (University of Hawai'i Press, 1990)
The relationship of overseas Chinese to the Chinese revolution of 1911 has always been viewed in light of their involvement with Sun Yat-sen. Of equal significance, however, was the growth and development in overseas communities of the radical reform party of K'ang Yu-wei and Liang Ch'ich'ao, pro-Sun revolutionaries, and other political groups greatly influenced the involvement of Chinese immigrants in the 1911 revolution and produced substantial changes in the overseas communities themselves. Chinese in the Americas, especially North America and Hawaii, provide a good illustration of these points but until now have received little attention. Revolutionaries, Monarchists, and Chinatowns provides a comprehensive and original treatment of this dimension of Asian American politics. L. Eve Armentrout Ma has judiciously analyzed the abundant documentation on the development and functioning of the reform and revolutionary parties, showing the interactions between the two parties and with pre-existing social organizations such as hui-kuan, surname associations, and Triad lodges. Particularly important is her use of the contemporary Chinese-language newspapers, a rich source of information on the period.